24.2k views
1 vote
Match the following differential equations with their solutions. The symbols A, B, C in the solutions stand for arbitrary constants. You must get all of the answers correct to receive credit.

1. d^2y/dx^2 + 25y = 0
2. dy/dx = 2xy/x^2 - 5y^2
3. d62y/dx^2 + 16 dy/dx + 64y = 0
4. dy/dx = 10xy
5. dy/dx + 24x^2y = 24 x^2
A. y = Ce^-8x^3 + 1
B. 3yx^2 - 5y^3 = C
C. y = Ae^-8x + Bxe^-8x
D. y = Ae^5x^2
E. y = A cos(5x) + B sin(5x)

1 Answer

5 votes

Answer:


1 \rightarrow E, 2\rightarrow B, 3\rightarrow C, 4\rightarrow D, 5\rightarrow A

Explanation:

1.
(d^2y)/(dx^2)+25y=0

The characteristic equation for the given differential equation is:


r^(2) +25=0


\Rightarrow r^2=-25


\Rightarrow r=\pm 5i

Since the roots are complex

Now, the general solution is:


y=A\cos 5x+B\sin 5x

2.
(dy)/(dx)=\frac {2xy}{x^2}-5y^2


\Rightarrow (dy)/(dx)-\frac 2xy=-5y^2

Divide both sides by
y^(-1)

Let,
v=y^(-1) \Rightarrow (dv)/(dx)=-y^(-2)(dy)/(dx)


\Rightarrow -(dv)/(dx)-\frac 2xv=-5


\Rightarrow (dv)/(dx)+\frac 2xv=5

Here,
p(x)=\frac 2x\; \text{and}\;\; q(x)=5

I.F.
=e^(\int \frac 2xdx)=x^2

Now, the general solution is:


vx^2=\int x^2 5dx=\frac {5x^3}3+c


\Rightarrow \frac {x^2}y-\frac {5x^3}3=c


\Rightarrow 3x^2-5x^3y=Cy

3.
(d^2y)/(dx^2)+16(dy)/(dx)+64y=0

The characteristic equation is:


r^2+16r+64=0


\Rightarrow r^2+8r+8r+64=0


\Rightarrow r(r+8)+8(r+8)=0


\Rightarrow (r+8)(r+8)=0


\Rightarrow r=-8,-8

Since the roots are real and repeated.

Now, the general solution is:


y=Ae^(-8x)+Bxe^(-8x)

4.
\frac {dy}{dx}=10xy


\Rightarrow \frac {dy}{y}=10xdx

Integrating both sides


\int\frac {dy}y=\int 10xdx+\log c


\Rightarrow \log y=5x^2+\log c


\Rightarrow y=e^(5x^2)+c

5.
\frac {dy}{dx}+24x^2y=24x^2

Here,
p(x)=24x^2 \; \text{and}\;\; q(x)=24x^2

I.F.
= e^(\int 24x^2dx)=e^(8x^3)

Now, the general solution is:


y.e^(8x^3)=\int 24x^2 e^(8x^3)dx=24\int x^2e^(8x^3)dx

Let,
8x^3=t \Rightarrow 24x^2dx=dt\Rightarrow x^2dx=\frac {dt}{24}


\Rightarrow ye^(8x^3)=\int e^tdt


\Rightarrow ye^(8x^3)=e^(8x^3)+c


\Rightarrow y=1+ce^(-8x^3)

User Harsh Nagarkar
by
4.8k points